CgNPG1 as a Novel Pathogenic Gene of Colletotrichum gloeosporioides From Hevea brasiliensis in Mycelial Growth, Conidiation, and the Invasive Structures Development - Liang, Chen; Zhang, Bei; Zhou, Yun; Yin, Hongyan; An, Bang; Lin, Daozhe; He, Chaozu; Luo, Hongli (Frontiers in Microbiology, 2021)
Rubber tree (Hevea brasiliensis) is a tropical perennial crop for primary source of natural rubber. Colletotrichum gloeosporioides Hevea brasiliensis (C. gloeosporioides Hb) and Colletotrichum acutatum Hevea brasiliensis (C. acutatum Hb) are the causal agents of rubber tree anthracnose and lead to serious loss of natural rubber production. Inoculation tests showed that C. gloeosporioides Hb possessed higher pathogenicity than C. acutatum Hb to rubber tree. Genomic analysis revealed that an unknown gene, named CgNPG1 (a Novel Pathogenic Gene 1), was presented in the genome of C. gloeosporioides Hb but not identified in C. acutatum Hb. CgNPG1 was predicted to encode a small secretory protein without any conserved domain. To investigate the functions of CgNPG1 in C. gloeosporioides Hb and in C. acutatum Hb, the gene deletion and overexpression mutants were generated. The phenotype analysis showed that deletion of CgNPG1 led to changed conidia morphology, decreased mycelial growth, conidiation, conidia germination rate, appressorium formation rate, and pathogenicity of C. gloeosporioides Hb to rubber tree. Meanwhile, heterogeneous expression of CgNPG1 in C. acutatum Hb significantly changed the conidia morphology and improved the mycelial growth rate, conidiation, conidia germination rate, appressorium formation rate and the pathogenicity of C. acutatum Hb to rubber tree. Consistently, CgNPG1 increased the expression level of CaCRZ1 and CaCMK1 in C. acutatum Hb. These data suggested that CgNPG1 contributed to mycelial growth, conidiation, the development of invasive structures and the pathogenicity of Colletotrichum to rubber tree, which might be related to the modulation of CaCRZ1 and mitogen activated protein kinase CMK1. Our results provided new insight into CgNPG1 in regulating growth and pathogenicity of Colletotrichum spp.